Do anátema ao acolhimento pastoral: da condenação e exclusão eclesial do Padre Cícero do Juazeiro à sua reabilitação histórica - Santana, Manoel Henrique de Melo (2007)
This dissertation treats of Father Cícero's History, who lived between 1844 and 1934, in Ceará. Juazeiro was the village where he was a Priest, staying there until his your death. He built the church of Our Lady of the Pains, without, however, being the pastor. His presence would have been the one of a shepherd dedicated to the flock, exactly what the Church asked him, don't root the "Miracle" of the Host bloody in the bigot's mouth of the pious Maria de Araújo. This fact would transform Father Cicero´s life and subsequently make Juazeiro, into the Holly City, that attracts crowds of Pilgrims, who came from everywhere. Father Cícero saw himself, then, involved in many conflicts. Always missunderstood he was seen as a curse by the Church. In practice, he was "excommunicated ", however, he was not aware of any formal excommunication. Simultaneously protected and condemned by many, it was the pilgrims however, who sustained the favoravle reputation of Father Cícero and Juazeiro, by fidelity and peaceful resistance. The desire of historical rehabilitation, both pastoral and ecclesiastical grew inside the Catholic Church. In an official way, the Vatican´s request, coordinated by the diocesan Bishop, Dom Fernando Panico, started the process of historical rehabilitation of Father Cícero. Looking for the reasons that reasons that motivated the change of the "curse into the pastoral reception , was the major objective of our research